Do Spiritual Values Matter? Examining the Role of Mobile Banking Features and User Experience in Driving Customer Satisfaction and Loyalty - Happy Adi Nugroho; Anies Lastiati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates the impact of mobile banking features and user experience on customer loyalty in Islamic banking, with customer satisfaction as a moderating factor and spiritual value as a moderator. A quantitative approach was applied by surveying 196 Islamic bank customers in Jabodetabek, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that both mobile banking features and user experience significantly enhance customer satisfaction and loyalty. Customer satisfaction also mediates the relationship between service quality and loyalty. However, spiritual value does not significantly moderate the relationship between mobile banking features or user experience and satisfaction, suggesting that customer evaluations are more influenced by functional and technical aspects than spiritual factors. These findings contribute to Islamic digital banking literature and highlight the need for banks to prioritize innovation, system reliability, and user-friendly design while maintaining Sharia compliance as a minimum standard.